The dynamics of solo self-employment: Persistence and transition to employership - Daniel S. J. Lechmann; Christoph Wunder (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
This study examines dynamics of solo self-employment. In particular, we investigate the extent of true state dependence and cross state dependence, i.e., whether experiencing solo selfemployment causally affects the probability of becoming an employer in the future. We use data from the German Socio-Economic Panel to estimate dynamic multinomial logit models. Our results show that the extent of true (cross) state dependence is rather small. The observed persistence in solo self-employment as well as transitions from solo self-employment to employership can largely be explained by observed and unobserved heterogeneity.
Keywords: J23; J62; 330; state dependence; dynamic multinomial logit; solo self-employment; own-account worker; stepping stone; German SOEP